Urgency for Inter-State Dialogue for Fighting Terrorism in South Asia - Umbreen Javaid (Journal of Political Studies, 2011)
South Asia today is in limelight of the world again, this time due to the ongoing terrorism in the region. Amongst other states in this region are India and Pakistan, the two antagonist and nuclear neighbors. The relations between the two countries are marred with tensions, conflicts and wars. At present the ongoing bilateral dialogue and peace process has once again been disrupted due to rising tensions between the two regarding cross border terrorism. This study attempts to investigate why there is urgency for interstate dialogue between India and Pakistan. The paper further highlights how the issue of terrorism has adversely affected the peace efforts between the two countries and also the overall peace and security of South Asia. The paper concludes with the outcome that terrorism in the region can only be curtailed with joint efforts especially with regard to India and Pakistan.